LEADERSHIP AND MANAGEMENT IN THE DIGITAL AGE: STRATEGIES FOR TECH-DRIVEN ORGANIZATIONS - Agrawal, Akash Deepak (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the digital age, leadership and management practices in tech-driven organizations are undergoing a profound transformation, driven by advancements in artificial intelligence, big data analytics, cloud computing, and agile methodologies. This study explores the impact of digital transformation on organizational leadership, highlighting its role in enhancing productivity, decision-making speed, and financial performance. The findings reveal a 15.42% increase in productivity, a 10.60-day reduction in decision-making time, and an average revenue growth of 28.27%, demonstrating the effectiveness of digital leadership strategies. A moderate positive correlation (0.26) between productivity improvements and revenue growth further emphasizes the importance of workforce efficiency in achieving financial success. To sustain competitive advantage, organizations must invest in digital leadership training, technological innovation, cybersecurity, and adaptive management strategies. This study concludes that embracing digital transformation is essential for modern organizations to drive innovation, enhance workforce engagement, and navigate the evolving business landscape successfully.